Serial MRI and MRS studies with unusual findings in Rasmussen's encephalitis - TÜRKDOĞAN, DİLŞAD (SPRINGER VERLAG, 2000)
Rasmussen's syndrome is characterized by intractable seizures and progressive neuropsychiatric deterioration secondary to unilateral cortical inflammation and tissue destruction. Diagnosis of Rasmussen's syndrome in the early phase depends mainly on the clinical features. Neuroimaging and histopathologic examinations may not be specific during this period. We report a case of Rasmussen's syndrome followed by serial MRI and magnetic resonance spectroscopy (MRS) studies over a 3- to 16-month period. A healthy 6-year-old boy presented with focal motor seizures. An MRI study demonstrated prominent enlargement and T2 hyperintensity of the left mesial temporal lobe and perisylvian region. This early finding evolved to volume loss and later progressive atrophy of the ipsilateral hemisphere when epilepsia partialis continua occurred. Being aware of those early MRI features in a patient with increasing frequency of focal motor seizures should suggest Rasmussen's syndrome. In addition, we found prominently increased myoinositol concentration in atrophic cortex which might reflect increased gliosis in the late period of the disease.
Keywords: Rasmussen's syndrome; neuroimaging early findings; myoinositol; STATUS EPILEPTICUS; BRAIN-TUMORS; SPECTROSCOPY